Gereja Tanpa Mimbar: Sebuah Model Kepemimpinan Eklesial Feminis - RJ Natongam Sianturi (IAKN TORAJA, 2020)
Abstract: Patriarchy culture has strongly influenced the Christianity on marginalizing women, especially limiting women's leadership in the church. Biblical theorems and the church fathers' views that subordinate women are also used as reasons to perpetuate male power in the church. Women are not only blamed for being considered the origin of sin, but also seen as weak, inferior, lustful, more emotional, and less rational than men. Although the Bible also records that there were women who became apostles and leaders, but this fact did not necessarily undermine the patriarchy culture in the church. Based on that, the author criticizes the patriarchy culture in the church and reconstructs a model of church leadership that sides with women. In this article, the author proposes a church without a pulpit as a feminist ecclesial leadership model with several concepts, namely (1) the church is women and women are the church; (2) the church as a common space; (3) the church as a space for friendship; and (4) the church as a space for sharing. Keywords: leadership, women, feminist, ecclesiology. Abstrak: Budaya patriarki secara kuat memengaruhi Kekristenan untuk memarginalkan perempuan terkhusus membatasi kepemimpinan perempuan di dalam gereja. Dalil-dalil Alkitab dan pandangan Bapa-bapa gereja yang mensubordinasikan perempuan juga turut digunakan sebagai alat untuk melanggengkan kekuasaan laki-laki di dalam gereja. Perempuan tidak hanya disalahkan karena dianggap sebagai asal dosa namun juga dipandang lebih lemah, lebih rendah, makhluk hawa nafsu, lebih emosional, dan kurang rasional dibandingkan dengan laki-laki. Walaupun Alkitab juga mencatat ada perempuan yang menjadi rasul dan pemimpin, namun fakta ini tidak dapat meruntuhkan budaya patriarki di dalam gereja. Berdasarkan itu, penulis mengkritisi budaya patriarki di dalam gereja dan merekonstuksi model kepemimpinan gereja yang berpihak kepada perempuan. Dalam artikel ini, penulis menggagas gereja tanpa mimbar sebagai model kepemimpinan eklesial feminis dengan beberapa konsep, yaitu (1) gereja adalah perempuan dan perempuan adalah gereja; (2) gereja sebagai ruang bersama; (3) gereja sebagai ruang persahabatan, dan (4) gereja sebagai ruang berbagi. Kata kunci: kepemimpinan, perempuan, feminis, eklesiologi.